Mindfulness as adjuvant therapy for chronic pain - Mindfulness come terapia adiuvante in pazienti affetti da dolore cronico - Matteo L.G. Leoni; Laura Bardetti; Roberta Venturi; Fabrizio Micheli (Publiediting, 2019)
Mindfulness is a psychological treatment frequently used for the management of psychological distress, depressive symptoms and anxiety. It seems to work by refocusing the mind on the present with an increased awareness of inner sensations. Early mindfulness studies in chronic pain patients showed promising outcomes on pain and psychological symptoms even if the scientific evidence is poor due to methodological problems. The aim of this study was to find which chronic pain patients attending a self-help group would have chosen to practice mindfulness if they were asked and if there were prior individual features that made a patient best suited to this treatment. Our results suggest that only patients characterized by low levels of anxiety, depression and discomfort and high levels of wellness at CBA-VE score (Cognitive Behavioral Assessment) accepted to practice mindfulness. CBA-VE was able to differentiate between patients that accepted to practice mindfulness and who did not.